Ratiometric Fluorescent Biosensors for Glucose and Lactate Using an Oxygen-Sensing Membrane - Duong, Hong Dinh (Biosensors (Basel), 2021)
In this study, ratiometric fluorescent glucose and lactate biosensors were developed using a ratiometric fluorescent oxygen-sensing membrane immobilized with glucose oxidase (GOD) or lactate oxidase (LOX). Herein, the ratiometric fluorescent oxygen-sensing membrane was fabricated with the ratio of two emission wavelengths of platinum meso-tetra (pentafluorophenyl) porphyrin (PtP) doped in polystyrene particles and coumarin 6 (C6) captured into silica particles. The operation mechanism of the sensing membranes was based on (i) the fluorescence quenching effect of the PtP dye by oxygen molecules, and (ii) the consumption of oxygen levels in the glucose or lactate oxidation reactions under the catalysis of GOD or LOX. The ratiometric fluorescent glucose-sensing membrane showed high sensitivity to glucose in the range of 0.1–2 mM, with a limit of detection (LOD) of 0.031 mM, whereas the ratiometric fluorescent lactate-sensing membrane showed the linear detection range of 0.1–0.8 mM, with an LOD of 0.06 mM. These sensing membranes also showed good selectivity, fast reversibility, and stability over long-term use. They were applied to detect glucose and lactate in artificial human serum, and they provided reliable measurement results.